Uncovering strategies and decision-making approaches of grade xi students on pisa problems - Arianti, Putri Dwi; Masamah, Ulfa (Pusat Studi Pengembangan Pembelajaran Matematika, 2026)
Mathematical decision-making skills are required when students encounter tasks that demand information filtering and appropriate procedural choices, such as those found in PISA. This study aims to describe how Grade XI students make mathematical decisions when solving PISA problems by examining the tendencies that appear at each stage of problem solving. The research employed a qualitative approach with a case study design, involving purposively selected participants. Data were collected through problem-solving tests and task-based interviews, and validated using triangulation of written responses, interview results, and researcher field notes. The findings show that intuitive subjects tend to make decisions quickly based on visual perception and spontaneous judgment without mathematical verification. Empirical subjects rely on visual inspection and prior experience supported by limited calculation. Heuristic subjects depend on general rules they perceive as applicable to the task structure, although this often leads to oversimplification. Rational subjects follow a structured process involving complete calculations and systematic comparison of alternatives before making a decision. These results indicate that variations in thinking strategies influence the accuracy of students’ mathematical decisions.